Radiographic Changes Five Years After Treatment of Meniscal Tear and Osteoarthritic Changes - Katz, Jeffrey N.; Collins, Jamie E.; Brophy, Robert H.; Cole, Brian J.; Cox, Charles L.; Guermazi, Ali; Jones, Morgan H.; Levy, Bruce A.; MacFarlane, Lindsey A.; Mandl, Lisa A.; Marx, Robert G.; Selzer, Faith; et al. (Arthritis care & research (2010), 2025)
Objective Meniscal tear in persons aged ≥45 years is typically managed with physical therapy (PT), and arthroscopic partial meniscectomy (APM) is offered to those who do not respond. Prior studies suggest APM may be associated with greater progression of radiographic changes. Methods We assessed changes between baseline and 60 months in the Kellgren‐Lawrence (KL) grade and OARSI radiographic score (including subscores for joint space narrowing and osteophytes) in subjects aged 45–85 years enrolled into a seven‐center randomized trial comparing outcomes of APM with PT for meniscal tear, osteoarthritis changes, and knee pain. The primary analysis classified subjects according to treatment received. To balance APM and PT groups, we developed a propensity score and used inverse probability weighting (IPW). We imputed a 60‐month change in the OARSI score for subjects who underwent total knee replacement (TKR). In a sensitivity analysis, we classified subjects by randomization group. Results We analyzed data from 142 subjects (100 APM, 42 PT). The mean ± SD weighted baseline OARSI radiographic score was 3.8 ± 3.5 in the APM group and 4.0 ± 4.9 in the PT group. OARSI scores increased by a mean of 4.1 (95% confidence interval [95% CI] 3.5–4.7) in the APM group and 2.4 (95% CI 1.7–3.2) in the PT group (P < 0.001) due to changes in the osteophyte component. We did not observe statistically significant differences in the KL grade. Sensitivity analyses yielded similar findings to the primary analysis. Conclusion Subjects treated with APM had greater progression in the OARSI score because of osteophyte progression but not in the KL grade. The clinical implications of these findings require investigation.